О модели русского словосложения с глагольной препозицией в сравнении с итальянской моделью - Федорова, Людмила (Studia Rossica Posnaniensia, 2020)
The paper is supposed to consider the formation of Russian compounds based on the imperative construction in comparison with a similar model in Italian. It is believed that in literary Russian this model is not productive, although it occurs in a limited number of examples: for the evaluative names of persons (sorvigolova ‘daredevil’), for the names of animals and plants (vertišejka, perekati-pole) and in some other cases. However, in Romance languages, and particularly in Italian, this is one of the most productive models, although its grammatical status is not usually associated with the imperative construction. As for Russian, it is possible to assume a transformation of the imperative sentences and imperative meaning, and only a particular modal shade of typical actions is preserved. The model itself is represented as a transition from incomplete compounding to the canonical productive model with an interfix. The results of an experiment on the translation of Italian compounds into Russian nonce compounds show a number of transitional cases, supporting this hypothesis.